Pemphigus foliaceus in Arabian oryx (Oryx leucoryx). Issue 6 (November 2021) - Curtiss, Jeffrey B.; Lewis, Michelle; Mitchell, Emily P.
Pemphigus foliaceus (PF) is an autoimmune acantholytic skin disease described in humans, dogs, cats, horses, goats, and sheep. From 2003 to 2016, six Arabian oryx ( Oryx leucoryx ) at the National Zoological Garden in Pretoria, South Africa, developed progressive, bilaterally symmetrical, hyperkeratotic skin lesions and pustules consistent with PF. Lesions were similar to those observed in domestic animals and primarily affected the pinnae, face and nasal planum, distal legs, and tail tip. Histological evaluation of suspect PF skin lesions in affected animals, evaluation of medical records for treatments received, causative agents in the diet and environment, and special stains for infectious organisms yielded no consistent inciting cause. The Arabian oryx is a species highly adapted to arid environments of the desert and has recently survived from a severe genetic bottleneck; both of these factors may have contributed to the development of PF in these animals.